(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
We know that around the world, pictographic writing has become important as a universal language that supports communication between people. It has proven to be easy for everyone in the world to convey information and communicate in multiple languages. Pictograms are simple graphic representations of the objects they represent. Universally sized icons and symbols go some ways to justify the saying "A picture is worth a thousand words". This article provides reasonable information about the importance and effectiveness of pictograms in today’s study of their place, importance and meaning, in the process of information sharing and interpretation in people’s lives.